Pengembangan Model Desain Konseptual Manajemen Pelatihan Seni Rupa Guru Taman Kanak-Kanak Kota Semarang - R, Sri Verayanti (Manajemen Pendidikan, 2014)
The background of this research has not managed with maximum visual arts training, duties of the demands of teachers and kindergarten teachers are required to be creative in developing and making learning. The purpose of this study is to design a conceptual model development forms management valid  art training at the kindergarten teachers, include; (a) the development of a model management plan for the training of kindergarten teachers of art, which consists of identifying needs, the goal of training and preparation of training packages; (b) the development of management training for the implementation of the model that consists of a kindergarten teacher competence standard, basic competence, guidelines and training modules; (c) the development of evaluation model of management training for kindergarten teachers of art, covering the reaction and impact of training. The research method is the Research and Development (R & D). The respondents were a kindergarten teacher in the city of Semarang. This MPSR model design through stages namely; (1) analyze the empirical models MPSR kindergarten art teacher Semarang (2) to analyze the needs of kindergarten teachers MPSR Semarang; MPSR model design is influenced by three factors; (1) training materials; (2) instructor competence, and (3) management training. MPSR model was designed using MPSR training support package consisting of; MPSR mananajemen guidebook and training module contains material MPSR art. Model MPSR refers manajamen function (planning 3 steps, namely: identification of training needs, setting training objectives and setting up training programs, (2) implementation consists of two steps, namely: the realization of the model, art competence training, and evaluation of training consists of; 2 steps namely, monitoring and evaluation of the reaction and the impact of training.